Implementation and Evaluation of User-Centered Design in an Online New Student Admissions System for Early Childhood Education - Zulvi, Mutia Sari; Najwa, Nina Fadilah; Ningsih, Nindi Lestia (Journal of Applied Informatics and Computing, 2025)
The new student admissions process is often conducted conventionally, requiring parents to visit educational institutions in person to submit physical documents. This approach tends to be inefficient, poses risks of document loss or damage, and slows down data analysis. Promotional methods relying on word-of-mouth and social media are also considered less optimal. To enhance efficiency and user experience, a web-based admissions system was developed using a User-Centered Design (UCD) approach. The UCD method was applied to understand the needs and characteristics of key users, including administrators, admissions committee members, school principals, and parents. The development process involved three iterations, covering user needs analysis, user experience-based interface design, testing, and repeated evaluations. The system includes features such as online registration, data management, a payment system, automated notifications, and geolocation to assist parents in estimating school distance. System evaluation using black-box testing and usability testing resulted in a System Usability Scale (SUS) score of 92.125, classified as "Excellent." These findings indicate that the UCD approach effectively produces systems that align with user needs and improve the efficiency of new student admissions.